New Materials and Flow Field Design for Middle‐Temperature Direct Methanol Fuel Cell with Low Cathode Pressure. Issue 3 (5th June 2019) - Gogel, V.; Sakthivel, M.; Bender, J.; Salzmann, B.; Kerres, J.; Scholta, J.; Drillet, J.‐F.
Abstract: A partially fluorinated polyether ionomer (SFS) has been prepared and blended with partially fluorinated polybenzimidazole (F6 ‐PBI), yielding acid‐base blend membranes with different weight ratios of the blend components. Best membranes in terms of conductivity and mechanical stability were characterized towards their solubility in methanol at high pressure and temperature as well as their ex situ and in situ conductivity. Optimized acid‐base SFS‐PBI blend membrane and carbon‐supported Pt3 Pd cathode catalyst were then tested in several DMFC cell designs. The results from preliminary membrane electrode assembly (MEA) tests turned out to be completely scalable from 25 cm 2 up to 100 cm 2 active area in a single‐cell configuration set‐up. During ultimate test in a 100 cm 2 4‐cell DMFC stack at 130 °C, a maximal power of about 60 W was yielded with methanol feed of 2.8 bar and air feed close to ambient pressure. This was possible due to repeated reduction of channel cross‐section geometry combined with forced convection effects that led to enhanced oxygen transport at rib/GDE interface and higher catalyst utilization in starve zones.